Inside Cover: Solid‐State NMR Spectroscopy Proves the Presence of Penta‐coordinated Sc Sites in MIL‐100(Sc) (Chem. Eur. J. 40/2017). Issue 40 (24th May 2017) - Giovine, Raynald; Volkringer, Christophe; Ashbrook, Sharon E.; Trébosc, Julien; McKay, David; Loiseau, Thierry; Amoureux, Jean‐Paul; Lafon, Olivier; Pourpoint, Frédérique
Abstract : The use of advanced solid‐state NMR methods, combined with first‐principles calculations, highlight for the first time the formation of penta‐coordinated scandium in activated Sc3 BTB2 and MIL‐100(Sc) MOFs upon dehydration. These coordinatively unsaturated sites correspond to the Lewis acid sites in MIL‐100(Sc), responsible for its catalytic activity. More information can be found in the Full Paper by F. Pourpoint et al. on page 9525 .